Cyber-Terrorism Law, Implementation and Ways Forward: Amir Shahzad - Shahzad, Amir (International Journal for Electronic Crime Investigation, 2019)
This research paper is concerned with focused critical analysis of cyber terrorism laws in Pakistan. Cyberspace is now becoming a battlefield where terrorists are active on dark net and using digital tunnel for which every country of the world has to take necessary steps for global peace, in the same way Pakistan needs an effective legislation and its efficient implementation. We explore here some crucial questions regarding cyberterrorism threats, cyber terrorism laws, implementation challenges and some recommendations based on current situation as well as a slight glance on future perspective of the topic Cyber terrorism law, implementation and the ways forward